Planes, ships and taxes: charging for international aviation and maritime emissions. Issue 76 (14th October 2013) - Keen, Michael; Parry, Ian; Strand, Jon
Summary International aviation and maritime transport account for a significant and growing share of global carbon emissions. Yet they are not only excluded from the Kyoto agreement and all current carbon pricing schemes, but do not even pay fuel excises of the type standard for other transport activities. Moreover, each sector benefits from preferential tax treatment – failure to charge VAT on international aviation, and the application of tonnage tax regimes rather than the normal corporate tax in maritime. This paper considers the design of fuel charges in these sectors to address these distortions, and quantifies their impact on emissions, revenue and welfare – showing, amongst other things, that the gain from offsetting the pre‐existing tax distortions may be as significant as those from reducing emissions. It shows, too, how compensation schemes can be designed to protect the poorest countries – a key ingredient in the politics of the issue, given the practical need for wide applicability of such charges. The real challenge is to amass the degree of international cooperation required (especially strong for maritime), failure of which to some degree explains their current under‐taxation – and, unsurprisingly, to decide who gets the money. Technically, these charges should, if anything, be rather easy to implement. <related-article related-article-type="source" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">— Michael Keen, Ian Parry and Jon Strand</related-article>